Drivers of fecundity in oviparous Lizards from arid an dean foothills: The case of a Liolaemus clade - Gallardo, Gabriela Alejandra (2023)
Environmental, morphological, and phylogenetic agents may explain the clutch size in lizards. Some lineages do not fit the established correlates, however, and the causes of the variations are poorly understood. We evaluated the fecundity (in terms of clutch size) of 20 oviparous Liolaemus lizards of the boulengeri group using environmental variables under a phylogenetic framework. We used Pagel’s Phylogenetic Signal Test to determine if the patterns observed respond to phylogenetic relatedness or other factors. We also ran phylogenetic generalized least squares models to determine which variable better explains differences in clutch size in these species. We found that female body size showed a strong phylogenetic signal. The clutch size of these lizards is mainly related to the daily thermal amplitude and showed a weak phylogenetic signal. Female body size weakly explains fecundity at the lineage level. It seems that thermal amplitude and, to a lesser degree, female body size and relative humidity are the critical factors for clutch size in these lizards, probably because it provides the females the conditions to reach a better body condition for reproduction.